Tsunami Modelling Araound Lombok, Indonesia - Indriati Retno Palupi, Wiji Raharjo (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Lombok earthquake in 2018, raised many failure of facilities that impact to human life. The earthquake was unique, started with mainshock that did not predict by scientist with hypocenter located in Flores Fault in the north of Lombok Island. In 1992, tsunami recorded in Lombok with the hypocenter also in Flores Fault. Based on the information, earthquake in Flores Fault can trigger tsunami. Beside Flores Fault, subduction zone in the south of Lombok is also can be earthquake source and it is not impossible can trigger the tsunami. The purpose of this research is to modeled the tsunami both it come from earthquake in Flores Fault and the subduction zone with magnitude 7.8. Numerical method is used to modelled it and the result is the height and velocity of tsunami is 11 m and 720 km/hours for Flores Fault and 9 m and 450 km/hour for subduction Zone.